2020
DOI: 10.1021/acsaelm.0c00311
|View full text |Cite
|
Sign up to set email alerts
|

Approaches to Measure the Resistivity of Grain Boundaries in Metals with High Sensitivity and Spatial Resolution: A Case Study Employing Cu

Abstract: It is well-known that grain boundaries (GBs) increase the electrical resistivity of metals due to their enhanced electron scattering. The resistivity values of GBs are determined by their atomic structure; therefore, assessing the local resistivity of GBs is highly significant for understanding structure–property relationships. So far, the local electrical characterization of an individual GB has not received much attention, mainly due to the limited accuracy of the applied techniques, which were not sensitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 41 publications
(117 reference statements)
1
23
1
Order By: Relevance
“…By averaging over seven measurements in different wires, they obtained a grain-boundary resistivity value ρ SGBR 1.06(10) × 10 -16 m 2 for the incoherent 3 {211} grain boundary. In view of the < ρ SGBR (Cu) >~3 × 10 -16 m 2 value for average random grain boundaries (see Table 2), the result of Bishara et al [53] is very reasonable (we will later compare it also to available theoretical values).…”
Section: Experimental a And ρ Sgbr Data For Ni And Cusupporting
confidence: 59%
See 4 more Smart Citations
“…By averaging over seven measurements in different wires, they obtained a grain-boundary resistivity value ρ SGBR 1.06(10) × 10 -16 m 2 for the incoherent 3 {211} grain boundary. In view of the < ρ SGBR (Cu) >~3 × 10 -16 m 2 value for average random grain boundaries (see Table 2), the result of Bishara et al [53] is very reasonable (we will later compare it also to available theoretical values).…”
Section: Experimental a And ρ Sgbr Data For Ni And Cusupporting
confidence: 59%
“…The physical picture behind the Andrews approach [15] is that we can assign a definite resistivity value to the unit surface area of a grain boundary, the latter considered as a wall of finite thickness. As discussed above, delicate measurements [43,[51][52][53] have demonstrated that, indeed, there is a definite resistivity increment when measuring the resistivity of a thin strip specimen containing a single grain boundary in comparison with an identical strip without grain boundary.…”
Section: General Comments On the Two Data Evaluation Approaches And On Matthiessen's Rulementioning
confidence: 93%
See 3 more Smart Citations